Discourses of Paganism in the British and Irish Press During the Early Pagan Revival - Wheeler, G. J. (Pomegranate, 2017)
This paper aims to investigate popular conceptions of Paganism in Great Britain and Ireland during the early phases of the Pagan revival. It focuses specifically on the languages through which modern Paganism was articulated in contemporary newspaper and magazine articles. Drawing on the conceptual framework provided by Ronald Hutton, it seeks to map out the tangle of discourses from which modern perceptions and self-perceptions of revived Paganism emerged.